2006
DOI: 10.5920/mhldrp.2006.32107
|View full text |Cite
|
Sign up to set email alerts
|

Deliberate Self Harm in Children and Adolescents

Abstract: This study compared children and adolescents who had deliberately selfharmed (DSH) with those who had not using data routinely collected during assessment at a Child and Adolescent Mental Health Service (CAMHS). The DSH group consisted of 64 boys and 194 girls aged between 7 to 18 years. The control group consisted of 175 boys and 181 girls aged between 11 and 18.As in previous studies, there was a substantially higher proportion of girls who self-harmed or who had depressive symptoms when compared to boys. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Previous studies have identified a range of barriers including increased time demands on therapists and administrative staff, a lack of therapist training on how to integrate measures into practice, a lack of data management systems with which to record, review and audit the data, and a perceived lack of clinically useful information, 60 for example if they did not include items to assess suicidal risk. 61 The qualitative interviews that were conducted within this study indicated that therapists recognised the value of sessional measures that accurately captured the problem and helped guide treatment, but they expressed worries about the measures' acceptability to young people. Notably, in addition to the social anxiety and intervention process measures, we added a further depression measure to the one that is used within the CYP IAPT data set (RCADS) to ensure that we routinely asked about suicidal risk (via the PHQ-9).…”
Section: Broader Implications For Treatment Delivery Within Child and Adolescent Mental Health Servicesmentioning
confidence: 91%
“…Previous studies have identified a range of barriers including increased time demands on therapists and administrative staff, a lack of therapist training on how to integrate measures into practice, a lack of data management systems with which to record, review and audit the data, and a perceived lack of clinically useful information, 60 for example if they did not include items to assess suicidal risk. 61 The qualitative interviews that were conducted within this study indicated that therapists recognised the value of sessional measures that accurately captured the problem and helped guide treatment, but they expressed worries about the measures' acceptability to young people. Notably, in addition to the social anxiety and intervention process measures, we added a further depression measure to the one that is used within the CYP IAPT data set (RCADS) to ensure that we routinely asked about suicidal risk (via the PHQ-9).…”
Section: Broader Implications For Treatment Delivery Within Child and Adolescent Mental Health Servicesmentioning
confidence: 91%
“…Additional barriers are related to limitations of the available outcome measures, for example, the fact that generic outcome measures do not typically assess self-harm behaviour and suicidal risk [ 30 ], or are not sensitive to symptom change in some clinical presentations [ 31 ].…”
Section: Barriers To the Implementation Of Rom Into Clinical Practicementioning
confidence: 99%
“…Johnston and Gowers [ 3 ] found that clinicians who did not regularly use quantitative clinical measurements were more likely to be sceptical about the value of the quantitative ‘medical’ approach. Additional concerns relate to ‘ labelling’ patients [ 30 ], confidentiality [ 23 ], and the risk of data being used by managers and commissioners to unfairly compare services that deal with different levels of case complexity [ 23 , 24 , 32 ]. Despite these reservations, most studies [ 2 , 24 , 36 ] report a range of clinicians’ views, with a substantial number of clinicians showing a positive attitude towards the implementation of ROM.…”
Section: Barriers To the Implementation Of Rom Into Clinical Practicementioning
confidence: 99%